Two-way exchanges between animal and plant biology, with focus on evo-devo - Minelli, Alessandro (Frontiers in Ecology and Evolution, 2022)
By definition, biology is the science of all living beings. However, horizons restricted to either plants or animals have characterized the development of life sciences well beyond the emergence of unified perspectives applying to all forms of life, such as the cell theory or the theory of evolution. Separation between botanical vs. zoological traditions is not destined to go extinct easily, or shortly. Disciplinary isolation is emphasized by institutional contexts such as scientific societies and their congresses, specialist journals, disciplines recognized as teaching subjects and legitimate and fundable research fields. By shaping the personal agendas of individual scientists, this has a strong impact on the development of biology. If in some fields, botanical and zoological contributions are since long effectively intertwined, in many others however plant and animal biology still fail to go beyond a marginal dialogue. Characteristically, the so-called 'general biology' and the philosophy of biology are still zoocentric (and often vertebrato- or even anthropocentric). I discuss legitimacy and fruitfulness of some old lexical and conceptual exchanges between the two traditions (cell, tissue, embryo). Finally, moving to recent developments, I compare the contributions of plant vs. animal biology to the establishment of evolutionary developmental biology. We cannot expect that stronger integration between the different strands of life sciences will soon emerge by self-organization, but opening the eyes on this persisting unbalance between plant and animal biology will arguably foster progress.